Orofacial myofunctional and polysomnographic characteristics of children with Down syndrome and obstructive sleep apnea: a pilot study - e Silva, Danielle Barreto [UNESP]; de Castro Corrêa, Camila [UNESP]; Weber, Silke Anna Theresa [UNESP] (FapUNIFESP (SciELO), 2024)
Purpose: To investigate oropharyngeal structures and functions in a pediatric population with Down Syndrome (DS) and obstructive sleep apnea (OSA) and to correlate with the apnea/hypopnea index (AHI) and sleep questionnaires. Methods: 12 Children with DS and OSA, between the age of 4 and 12 years old, underwent polysomnography (PSG); sleep questionnaires, Pediatric Sleep Questionnaire (PSQ) and Obstructive Sleep Apnea-18 (OSA-18); and speech-language evaluation using the Short Evaluation of Orofacial Myofunctional Protocol (ShOM). Results: There was a positive correlation between ShoM higher scores and the apneahypopnea index (AHI) and between ShoM and the number of hypopneas. The orofacial myofunctional alterations observed in the studied group were: oral breathing, alteration in lip tonus and competence, tongue posture at rest and in swallowing, and occlusal alteration. There was also an increased risk for OSA according to the sleep questionnaires, as well as the presence of obesity and overweight, but without correlation with the severity of OSA. Conclusion: All DS children show alterations in orofacial characteristics, higher scores being associated to severe OSA. Orofacial myofunctional evaluation may help to identify different phenotypes in Down syndrome children with Obstructive sleep Apnea, enhancing the need for a multidisciplinary approach.
Características miofuncionais orofaciais e polissonográficas de crianças com Síndrome de Down e apneia obstrutiva do sono: estudo piloto
Keywords: Child; Down Syndrome; Language and Hearing; Obstructive; Polysomnography; Sciences; Sleep Apnea; Speech; Stomatognathic System